Brand Pushkar (Destination Branding on the Planks of Culture and Religious Hertiage as USP) - Premi, Rakesh (Indian Journal of Marketing, 2010)
Tirth Raj Pushkar, abode of Lord Brahma is a small town situated 14 kms. North West of Ajmer city (Rajasthan state) in the Aravali ranges and stands as a testimony to the rich culture of Rajasthan and religious heritage of India. It is considered as one of the most sacred place of Hindus and a holy dip in the Pushkar Lake is essential for all. A colorful and lively huge cattle fair is held every year on Kartik Purnima and lacs of pilgrims and ascetics gather here.